Undergraduates urged to sharpen soft skills, rise to excellence - UMP, PNC
The Minister of Higher Education, Dato’ Seri Mohamed Khaled Nordin, urges the 40,366 students, who have successfully secured their placements in the local institutions of higher learning (IPTs) nationwide, to rise to excellence and sharpen themselves with the necessary soft skills to evolve into becoming globally competitive graduates.